The Crisis and Miss Emily's Perceptions - Leruth, Luc (Departmental Papers; Departmental Paper ;, 2010)
The Crisis and Miss Emily's Perceptions draws an analogy between the theme and the characters in Faulkner's short story "A Rose for Emily" and the global financial crisis. In Faulkner's story, all the characters try to deny realities, thus allowing an unstable situation to last longer than it should have. The paper briefly reviews the literature on perception biases and argues that all economic actors have, to some degree, been refusing to face realities, which helped the crisis to unfold.